Brain parenchyma sonography in the study of movement disorders - Hernández-Vara, Jorge (Revista de neurologiá, 2010)
In the last decade the use of ultrasound imaging techniques in the evaluation of the neurological patient has sparked a growing amount of interest and such techniques are being used in an increasingly large number of applications, both from a diagnostic and a therapeutic point of view. In this paper we outline the current evidence available on the use of ultrasound imaging of brain parenchyma (UIBP) in the study of movement disorders, and the possible significance of the ultrasound imaging findings. To review the sonographic findings in Parkinson's disease (PD) and other movement disorders and the role this technique can play as a diagnostic support tool. The usefulness and significance of UIBP in PD and other movement disorders is assessed by reviewing the most significant papers published in the last two decades. Likewise, the possible perspectives and future applications of the above-mentioned technique are discussed. UIBP is a useful and promising tool for detecting alterations in the echogenicity of the substantia nigra in PD. Other pathologies also present characteristic sonographic patterns and can be a valuable aid in the process of reaching a differential diagnosis between PD and other rigid-akinetic syndromes. The hyperechogenicity of the substantia nigra could be used as a nigrostriatal vulnerability marker and be applied on a routine basis to detect subjects with a higher risk of developing PD. However, standardised consensus protocols need to be established in order to allow better use to be made of it.